Sexual Behavior of Adolescents: Risk Factors in Rural Areas - Ema Waliyanti; Ratna Ajeng Dewantari; Dewi Puspita; Harumi Iring Primastuti (Media Kesehatan Masyarakat Indonesia, 2023)
The percentage of adolescents who have actively engaged in sexual behavior before marriage is 4.92%. Adolescents living in rural areas are more likely to be exposed to risky behavior than those who live in urban areas. This study aims to identify the factors that influence risky sexual behavior among adolescents in rural areas. This study used a qualitative method with a phenomenological approach. Data were collected using in-depth interview techniques on 12 participants consisting of 7 adolescents and 5 parents in rural areas. The samples were selected using a purposive sampling technique. The validity of the data was carried out using source triangulation and peer debriefing. The thematic analysis was carried out using Open code 4.03 software. This study showed that perception is a factor that can influence adolescents to engage in risky sexual behavior. It includes perceptions of risky sexual behavior such as dating, the definition of risky sexual behavior, risk factors, sexual relationships, and sexually transmitted diseases. In addition, adolescents' perceptions of risky sexual behavior in health, psychology, education, and the future are also the factors that influence risky sexual behavior. Apart from the perception, other factors include discomfort feeling at home, sexual experience, the influence of social media, the influence of friends, love from partners, and environmental influences. Based on our results, the better the adolescent's perception of risky sexual behavior is, the lower the risk of adolescents engaging in risky behavior will be.